Enabling sustainable crop protection with induced resistance in plants - Flors, Victor; Kyndt, Tina; Mauch-Mani, Brigitte; Pozo, Maria J.; Ryu, Choong-Min; Ton, Jurriaan (Frontiers in Science, 2024)
Induced resistance (IR), which enables plants to increase their resilience against insect pests and microbial pathogens by promoting their own immunity, has been recognized for its value in crop protection schemes. Despite promising applications, the use of induced resistance in crop protection has remained marginal in comparison with the exploitation of pesticides and single resistance genes. This review aims to shed light on this disparity by examining the scientific milestones achieved over the past decades for both internal (immunological) and external (ecological) induced resistance strategies. Next, the multi-faceted advantages of IR, particularly its ability to provide broad-spectrum protection and enhance the nutritional and nutraceutical value of certain crops, are discussed. This study also reveals the various obstacles hindering the widespread adoption of induced resistance strategies. After considering recent scientific discoveries and insights, potential solutions are proposed, including leveraging epigenetic approaches, to understand the mechanisms involved in IR.By acknowledging that the future sustainability of crop protection is irreconcilable with single-use technologies, this review proposes taking advantage of the latest insights regarding the adaptive nature of the plant immune system and its ecological interactions to safely integrate induced resistance into existing crop protection schemes. By emphasizing the need for both comprehensive and holistic approaches to basic and translational research, this review sets the stage for leveraging induced resistance alongside other strategies to foster a resilient, environmentally friendly, and economically viable future, thereby ensuring the health of crops.